First Record of Cacopsylla pulchella (Hemiptera, Psyllidae) in Croatia - Milan Pernek; Marta Matek; Tamara MAretić; Nikola Lacković; Dinka Matošević (South-East European Forestry, 2020)
The aim of this study is to identify plant lice Cacopsylla pulchella a new alien insect in the fauna of Croatia. We propose a new method of infestation level assessment in order to assess the potential of this insect as a pest. In May 2020 samples were collected from eleven locations in Croatia, where Cercis siliquastrum is grown in parks. Adults and nymphs of C. pulchella were collected together with a plant material and brought to entomological laboratory for further analysis. Field research was performed in order to assess the distribution and infestation intensity across various localities in Croatia. The intensity of infestation was assessed heuristically by visual examination and was categorized in four categories: 0) no infestation, 1) low, 2) moderate and 3) high infestation. C. pulchella was confirmed on C. siliquastrum in eleven localities in Croatia. Most of the infested trees had a low or moderate intensity of infestation. Damages caused by this insect are due to the emission of honey dew, a small spherical drop covered with waxy secretion causing necrotic areas which could lead to the premature fall of the leaves. It is not known what kind of progress in infestation intensity could be expected so infested trees found in this study should be checked closely in the coming years. It is strongly suggested to continue the monitoring of this alien insect on C. siliquastrum in Croatia and to estimate its potential of become an invasive pest which could endanger ornamental and other values of its hosts.